Analysis of economic activity - Havrys, M. O.; Havrys, O. O. (My University, 2019)
Analysis of economic activity, which is also called the business analysis, is a system of special knowledge, based on the laws of development and functioning of systems and aimed at understanding the methodology of assessing, diagnosing and forecasting the financial and economic activities of an enterprise. "Analysis of economic activity" course of study is designed for both full time and correspondence students of the specialties 071 "Accounting and taxation" and 073 "Management". The subject of business analysis is the business processes of enterprises, their socio-economic efficiency and the final financial results of activity, which are formed under the influence of objective and subjective factors, which are reflected through the system of economic information.
Keywords: business analysis; balance; accounting; financial results